Rationale and design of the cyclosporine in Takotsubo syndrome (CIT) trial - Bruns, Bastian; Elsous, Nesrin; Burghaus, Ina; Steyrer, Kathleen; Joos, Maximilian; Krämer, Tobias; Scheffel, Marina; Blankenberg, Stefan; Eitel, Ingo; Maßberg, Steffen; Thiele, Holger; Meder, Benjamin; et al. (American heart journal, 2025)
Background - Takotsubo syndrome (TTS) is associated with substantial morbidity and mortality, even though ejection fraction frequently recovers spontaneously. TTS has been suggested to be caused by catecholamine excess leading to myocardial inflammation as an additional driver of cardiac damage and impaired outcome. Currently, no evidence-based treatment exists. In a preclinical model of catecholamine-driven TTS, cyclosporine A (CsA) bolus therapy significantly improved outcome, likely mediated via suppression of calcineurin-driven inflammation. The Cyclosporine In Takotsubo syndrome (CIT) trial is a pilot multicenter double-blinded randomized placebo-controlled trial (RCT) to investigate the impact of CsA bolus therapy in patients suffering from acute TTS. - Study design and objectives - This RCT is designed to investigate the impact of repetitive CsA bolus therapy vs. placebo in acute high-risk TTS patients with an increased risk of intrahospital complications and long-term mortality. The main goal is to reduce myocardial damage quantified by AUC of a centrally measured high-sensitive cardiac Troponin T (hs-cTnT) over 72 hours (primary endpoint). Therefore, patients with TTS will be randomized 1:1 after angiography and receive an intravenous bolus of 2.5 mg/kg CsA or an equivalent amount of placebo immediately after baseline measurements. At 12 and 24 hours additional doses of the study drug will be applied accumulating to 7.5 mg/kg in the intervention group. After baseline laboratory measurements (including hs-cTnT) and echocardiography (TTE), serum parameters will be measured again at 3 hours and every 12 hours from baseline. TTE imaging will be performed at 24, 48 and 72 hours, and cardiac magnetic resonance imaging (CMR) at 24 to 96 hours. Left ventricular function recovery, myocardial edema (CMR), in-hospital complications, length of hospital stay, 30-day and 1-year composite cardiovascular outcome, as well as Kansas City Cardiomyopathy Questionnaire self-assessment are included as secondary endpoints. - Conclusions - The CIT trial is designed to assess the safety and potential benefit of CsA on hs-cTnT release as an established marker of myocardial injury in high-risk TTS patients. The results of this trial may reveal CsA as a first pathophysiology-driven treatment option of TTS and enable a phase III follow-up trial powered for clinical outcome parameters as primary endpoint. - Clinical trials identifier - NCT05946772.
Gesehen am 11.12.2025